Kombinasi Pupuk Organik Cair dan NPK: Sebagai Booster Pertumbuhan Bibit Kelapa Sawit di Pre Nursery - Manurung, Ramona; Parwati, Wiwin Dyah Ully; Syah, Ryan Firman (Program Studi Agroteknologi INSTIPER, 2023)
Liquid organic fertilizer provides nutrients, increases good microorganisms and improves the physical properties of the soil, especially when used in oil palm nurseries. This research was conducted with the aim of determining the effect of providing liquid organic fertilizer and NPK on the growth of oil palm seedlings in the pre-nursery. This research uses a factorial experimental method arranged in a Completely Randomized Design (CRD) consisting of two factors. The first factor is liquid organic fertilizer which consists of 4 levels, namely Control/no fertilizer, 3 ml, 5 ml 8 ml. The second factor is NPK which consists of 4 levels, namely N1: Control/no fertilizer, N2: 1 g/plant, N3: 2 g/plant, N4: 3 g/plant. Each treatment was repeated 5 times. The data obtained were analyzed using Analysis of Variance (anova) with a level of 5%. Data that were significantly different were further tested with DMRT at a level of 5%. The results showed that there was a real interaction between liquid organic fertilizer and NPK on stem diameter. The best growth of oil palm seedlings at a dose of 1 g NPK fertilizer with 8 ml liquid organic fertilizer showed a value of 7.06 mm, a 2 g dose of NPK with a control liquid organic fertilizer showed a value of 7.02 mm, a 2 g dose of NPK and a dose of liquid organic fertilizer 3 ml shows a value of 7.00 mm. Real interaction between liquid organic fertilizer and NPK on crown fresh weight diameter. NPK at a dose of 1 g and POC at a dose of 3 ml showed a value of 6.46 g. Providing liquid organic fertilizer did not have a real effect on oil palm seedlings, while NPK at a dose of 1 g/plant had an effect on oil palm seedlings.